Village Baseline Study: Site Analysis Report for Tra Hat Village, Vinh Loi, Bac Lieu, Viet Nam (VNM 03) - Truc, Ngo Thi Thanh; Phong, Ngo Dang; Nguyen, Thanh Binh; Chi, Truong Thi Ngoc; Duong, Le Minh; Yen, B.T.; Ferrer, Alice J. (2015)
This report presents data collected from the Village Baseline Study conducted on 2-4 October 2014 at the Tra Hat village, Vinh Loi district, Bac Lieu, Vietnam. Data were collected through focus group discussions and participatory resource mapping with community members in the village. The Village Baseline Study is part of the baseline activities conducted under the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS) in South East Asia. The purpose is to collect data for indicators that will allow site comparability and monitoring to assess changes in terms of food security and natural resource management across time. Results show that the men and women in Tra Hat village consider farmland, rivers and canals as important natural resources. The quality, however, of land, water and wildlife habitats has declined in the last decade along with the improvement of farming techniques and intensive use of chemical fertilizers and pesticides. Infrastructures such as roads, internal canals, hospitals, schools, water supply station and electricity transformer station have improved. The future is envisioned to have improved internal canals in farmlands and a developed irrigation system, dykes and sluices to support high agriculture production. Home garden diversification was also believed to enhance food security and improve livelihood resilience. To turn the vision into reality, the community expects support from the different organizations working in the area considering current impacts of salinity intrusion and sea level rise, the need interventions of CCAFS and its partners. Strengthening the irrigation system, improving local rice variety, and introducing modern farming techniques taking into account negative impacts of climate change are major recommendation for future intervention.